2016
DOI: 10.1021/acscatal.6b01105
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Neutrality: Maximizing Success in the Analysis of Transition-Metal Catalysts by MALDI Mass Spectrometry

Abstract: The elucidation of molecular identity is a central challenge in homogeneous transition-metal catalysis. Most exacting, despite advances in electrospray-ionization mass spectrometry (ESI-MS), are neutral complexes, which encompass the vast majority of metal catalysts. Insight into molecular constitution, readily achieved in other areas of the chemical sciences, is commonly thwarted by decomposition of inorganic and organometallic compounds, particularly for highly reactive species. MALDI-MS, where coupled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…The detection of ionized CTCs in LDI‐MS is quite unusual. CTCs are often employed for MALDI‐MS analysis of neutral and/or photosensitive compounds with the help of charge‐transfer matrices . However, the analyte‐matrix CTCs are not stable under LDI conditions and dissociate into the cation radical of the electron donor, observed in the positive detection mode, and the anion radical of the electron‐acceptor, detectable in the negative detection mode.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of ionized CTCs in LDI‐MS is quite unusual. CTCs are often employed for MALDI‐MS analysis of neutral and/or photosensitive compounds with the help of charge‐transfer matrices . However, the analyte‐matrix CTCs are not stable under LDI conditions and dissociate into the cation radical of the electron donor, observed in the positive detection mode, and the anion radical of the electron‐acceptor, detectable in the negative detection mode.…”
Section: Resultsmentioning
confidence: 99%
“…They also interfaced an inert atmosphere glove box with a matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) to overcome problems regarding decomposition during sample transfer to the source, as seen in Figure 7. 45,46 Using the above-mentioned MALDI setup, an oxygen-sensitive titanium (III) ethylene polymerization catalyst was analyzed, as seen in box for laser desorption/ionization MS of air-sensitive solids can be used if the user is worried about contamination from the matrix. 47 When a purge box is used, the air-sensitive sample is always under inert gas while transferring to the source.…”
Section: Matrix-assisted Laser Desorption Ionizationmentioning
confidence: 99%
“…But this situation has been remedied by the introduction of matrices suitable for organometallic compounds by Fogg and co‐workers, who have shown that unfunctionalized polyarenes such as anthracene and pyrene perform well as matrices for fragile metal complexes . Fogg also pioneered the fully integrated combination of mass spectrometer and full‐size glovebox, which is an essential adjunct for MALDI of highly air‐ and moisture‐sensitive compounds given the necessity of exposure to the atmosphere during sample preparation . Figure shows the MALDI‐TOF mass spectrum of a variety of ruthenium complexes.…”
Section: Matrix‐assisted Laser Desorption Ionization (Maldi)mentioning
confidence: 99%